A trick of the light : a Chief Inspector Gamache novel - Penny, Louise (Penny, Louise. Three Pines mystery., 2011)
Investigating a murder at a solo artist's Quebec village home, Chief Inspector Gamache and his team encounter deceptive nuances in the art world that distort every clue they find with tales of duality and broken hearts.